DETERMINANTS OFF COMPANY VALUE AND PROFITABILITY AS A MEDIATOR - Tomi Sutoro; Nella Yantiana; Sari Rusmita (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The purpose of this study was to determine the effect of profitability mediating company size and capital structure on company value in Industrial Companies Processing Raw Materials and Services in the Indonesia Stock Exchange. The population in this study was 60 companies, and the number of samples of these research companies was 36 companies selected using a purposive sampling method with criteria, namely companies that provide complete financial reports for 2018-2022 and conduct initial public offerings before 2018-2022. The data analysis technique used SPSS version 25: descriptive statistics, classical assumption test, multiple regression analysis, correlation coefficient and determination, hypothesis testing, Sobel test, and path analysis. The results showed that company size and capital structure positively affect profitability, and company size and capital structure positively affect company value; profitability mediates company size and capital structure and has a positive effect on company value.